AKUNTANSI: MODAL SOSIAL, SOSIAL EKONOMI, DAN IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT PUPUK KALIMANTAN TIMUR DI BONTANG - La Ode Hasiara (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
The research is aimed to find out: (1) the function of accounting in corporate social responsibility toward the surrounding societies, (2) social capital as a variety of different entities, with two elements in common: they all consist of some aspect of social structure, and they facilitate certain actions of actors-whether personal or corporate actors-within the structure, (3) the implementation of corporate social responsibility. Method used for the research is qualitative research. Researcher collected data based on interpretation and the depth and richness of data obtaining from the field. Research result indicated that (1) Corporate Social Responsibility (CSR) is a program conducted by a company as its social responsibility and awareness toward the society; (2) PT Pupuk Kaltim had fast and accurate strategy to win the competition; (3) PT Pupuk Kaltim had partnership with multi-stakeholders, such as Farmers, NGOs, firms, media, government, and higher education institutions) in order to gain power to win the competition. Conclusion. The essence of a multi partnership capital conducted by PT Pupuk Kaltim was community development program designed by involving various stakeholders. The partnership formed became effective, efficient due to continuous commitment and trust from the company to farmer and artisan (weaver), specifically.